Sistem Informasi Peminjaman Buku pada Perpustakaan SMP Negeri 1 Umalulu Menggunakan Codeignater - Putra Kurniawan Hanggawali; Yustina Rada; Raynesta Mikaela Indri Malo (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
The development of technology in Indonesia, particularly in the field of education, has made rapid progress through the integration of information systems. This system has become a crucial element in managing educational data and information, including student data, class schedules, and attendance records. However, challenges arise in the management of the library at SMP Negeri 1 Umalulu, which still relies on a manual book borrowing system, potentially leading to errors in data validation. This research responds to these challenges by developing a web-based book borrowing information system using the CodeIgniter framework and the waterfall development method. The main goal is to enhance the efficiency of book management and facilitate the book borrowing and returning processes. The implementation of the new system is expected to reduce errors in manual recording and create a more structured and responsive library environment for visitors. The resulting information system is anticipated to have a positive impact on library management efficiency, enrich the reader's experience, and improve information access. Thanks to the developers and all involved parties for the successful implementation of this system. Hopefully, this achievement will inspire further technological advancements in the education sector, providing additional benefits and fostering a better learning environment.